Stress response pathways in the male germ cells and gametes - Santiago, J. (2020)
The unfolded protein response (UPR) is a conserved and essential cellular pathway involved in protein quality control that is activated in response to several cellular stressors such as diseases states, ageing, infection and toxins. The cytosol, endoplasmic reticulum (ER) and mitochondria are continuously exposed to new proteins and in situations of aberrant protein folding; one of three lines of defence may be activated: (i) heat-shock response, (ii) mitochondrial UPR and (iii) ER UPR. These pathways lead to different signal transduction mechanisms that activate or upregulate transcription factors that, in turn, regulate genes that increase the cell's ability to correct the conformation of poorly folded proteins or, ultimately, lead to apoptosis. Despite the recent progress in understanding such biological processes, few studies have focused on the implications of the UPR in male infertility, highlighting the need for a first approach concerning the presence of these components in the male reproductive system. In testis, there is a high rate of protein synthesis, and the UPR mechanisms are well described. However, the presence of these mechanisms in spermatozoa, apparently transcriptionally inactive cells, is contentious, and it is unclear how sperm cells deal with stress. Here, we review current concepts and mechanisms of the UPR and highlight the relevance of these stress response pathways in male fertility, especially the presence and functional activation of those components in male germinal cells and spermatozoa.